Self‐Assembly of Hydroxyl Metal–Organic Polyhedra and Polymer into Cu‐Based Hollow Spheres for Product‐Selective CO2 Electroreduction. Issue 7 (19th April 2021) - Yang, Ru-Xin; Wang, Yi-Rong; Gao, Guang-Kuo; Chen, Lin; Chen, Yifa; Li, Shun-Li; Lan, Ya-Qian
Abstract : The electrochemical CO2 reduction reaction (CO2 RR), an elegant solution to mitigate the greenhouse effect and produce high‐value feedstock, has significant hurdles in selective production of target products. Herein, a series of Cu‐based hollow spheres is synthesized through the self‐assembly of hydroxyl metal–organic polyhedra and a polymer. The obtained materials with tunable morphology and compositions enable precise generation of varied products in a flow cell. Specifically, polymer‐induced sol–gel (PISG)‐3 shows 61.1% (−0.9 V, −143 mA cm −2 ) Faradaic efficiency (FE) of C2 H4 and negligible CH4, higher than that of PISG‐1 ( FE C 2 H 4 46.7%) with solid‐sphere morphology. Interestingly, the products can be well tuned from C2 H4 to CH4 by introducing CaCO3, along with increased hydrocarbon selectivity and CO2 reduction efficiency. Notably, PISG‐8 with modified composition displays drastically changed products ( FE CH 4 55.8% and FE C 2 H 4 22.2%, −162 mA cm −2, −0.9 V). As certified by density functional theory calculations, CaCO3 is proven to decrease the possibility for coexistence of two adjacent *CHO to restrain the dimerization process and enhance the CH4 selectivity. Abstract : A series of Cu‐based hollow spheres have been prepared through the self‐assembly of hydroxyl metal‐organic polyhedra and F127. CaCO3 is selected as the desired additive to modify the inherent property of Cu‐based hollow‐spheres. The resultant CaCO3 decorated hollow spheres enable fine‐tuning production of varied electroreduction products with largely increased hydrocarbon selectivity and CO2 reduction efficiency.